Efficient plasmonic emission by the quantum Čerenkov effect from hot carriers in graphene - Ido Kaminer (Nature Portfolio, 2016)
Graphene plasmons have gained significant interest thanks to their high field confinement and low phase velocity. Here the authors show theoretically that charge carriers propagating in graphene can excite plasmons through a quantum Čerenkov emission process in two dimensions, in the form of plasmonic shock waves.